2017
DOI: 10.1111/polp.12219
|View full text |Cite
|
Sign up to set email alerts
|

Making Soft Power Work: Theory and Practice in Australia's International Education Policy

Abstract: Policy makers around the world are increasingly concerned with the challenge of cultivating and capitalizing on soft power. Yet government efforts to increase others feelings of attraction toward their countries face conceptual and practical challenges. This article examines Australias attempt to operationalize soft power in Asia through its international education strategy. Drawing on interviews with key officials, we show how the design of Australias international education policy was consciously informed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the reviewed publications, efficiency is assessed through the country's success in foreign trade relations. Also, a sufficient number of publications are devoted to assessing the impact on the image of the state of the policy in the field of education [10], the level of SHS Web of Conferences 92, 0 (2021) Globalization and its Socio-Economic Consequences 2020 development of sports in the country and achievements at international competitions [11,12].…”
Section: Empirical Assessment Of the Impact Of Soft Power Instrumentsmentioning
confidence: 99%
“…In the reviewed publications, efficiency is assessed through the country's success in foreign trade relations. Also, a sufficient number of publications are devoted to assessing the impact on the image of the state of the policy in the field of education [10], the level of SHS Web of Conferences 92, 0 (2021) Globalization and its Socio-Economic Consequences 2020 development of sports in the country and achievements at international competitions [11,12].…”
Section: Empirical Assessment Of the Impact Of Soft Power Instrumentsmentioning
confidence: 99%
“…It is also worth mentioning countries with high cultural and political capital/power such as Brazil (Stuenkel ), Poland (Zarycki, Smoczyński, and Warczok ), and South Africa (Ogunnubi and Amao ). Finally, there are the cases of South Korea (Gray ), Singapore (Calder ), and Australia (Byrne, Tyler, and Harris Rimmer ; Laifer and Kitchen ), all displaying very high levels of generalized development while not being military or political powers. Besides, there are quite a few global processes that put a “badge” of modernity on a given country: for example, the Conference of the Parties of the United Nations Framework Convention on Climate Change and the UN‐led Intergovernmental Panel on Climate Change; the Paris Declaration on Aid Effectiveness (monitored by the OECD); the UN Millennium Development Goals, and the ensuing Sustainable Development Goals within the 2030 Agenda for Sustainable Development; and the Group of 20 (G20).…”
Section: Reflections On Modern State Identitymentioning
confidence: 99%
“…These developments resulted from diplomatic, rather than educational, goals: the New Colombo Plan is a 'signature' policy of the Department of Foreign Affairs and Trade, and not the Department of Education. Research into Australian government scholarship programmes for foreign students to study in Australia has shown that the anticipation of public-diplomacy outcomes from these programmes was always present.4 Academic analyses of the NCP have emphasized such goals (Laifer and Kitchen 2017;Byrne 2016;Lowe 2015). As Laifer and Kitchen (2017:815) note, 'the design of Australia's international education policy was driven by soft power considerations' .…”
Section: People-to-people Contact In Australia-asia Relationsmentioning
confidence: 99%